ANALYSIS OF MAL ADMINISTRATION IN THE PROCUREMENT OF GOODS/SERVICES TENDER PROCESS IN GORONTALO DISTRICT PROCUREMENT OF GOODS AND SERVICES - Suprianto Ali; Azis Rachman; Yosef Koton (LP2M Universitas Bina Mandiri Gorontalo, 2023)
ABSTRACT This study aims to analyze the occurrence of mal-administration that occurs in the tender process for the procurement of goods/services in the goods and services procurement section of the Gorontalo district government and aims to determine the inhibiting factors for the tender process for the procurement of goods/services in the procurement of goods and services, especially in the government. gorontalo district. Research method used is a qualitative research method with data collection techniques including: 1) observation; 2) interview; and 3) documentation. Activities in data analysis, namely: 1) data reduction stage; 2) data presentation stage; and 3) data verification stage. The results in this study are , as follows: 1) m al -a administration in the tender process for the procurement of goods/services in the goods and services procurement section of the Gorontalo district, seen from the aspect of inefficiency, still occurs. Mal-administration in the tender process for the procurement of goods/services in the procurement of goods and services in Gorontalo Regency, seen from the lengthy aspect of the procedure , is still going on. M al - administration in the tender process for the procurement of goods/services in the procurement of goods and services of Gorontalo district seen from the dishonesty aspect is quite good, because officials show good attitudes or behavior, although it seems that so far there are things that are often not accepted by participants tenders. Administrative malls in the tender process for the procurement of goods/services in the procurement of goods and services in the Gorontalo Regency seen from the aspect of covering up errors still occur. And competence in the form of knowledge and skills hinders the implementation of the tender process for the procurement of goods/services. Rapid changes in regulations hinder the implementation of the tender process for the procurement of goods/services